EFFECT OF EARLY WEANING ON CARCASS CHARACTERISTICS OF LARGE WHITE YORKSHIRE PIGS UNDER INTENSIVE SYSTEM* - ESWARA RAO5, V. SRAVANTHI1; D. SURESH BABU2 A. ANITHA3; P. ASHA LATHA4 (Indian Journal of Animal Production and Management, 2017)
A study was carried out in 54 Large White Yorkshire pigs to find out the effect of earlyweaning on carcass traits. Three weaning age groups namely group 1 ( 25 days ), group 2 (40 days) and group 3( 56 days ) were compared. Each group consists of 18 piglets fromthree litters. Five months after weaning, six pigs from each group were slaughtered and thecarcass traits studied included Pre-slaughter weight, Carcass length, Hot carcass weight,Average Back fat thickness, Dressing percentage, Meat-bone ratio and Whole sale primalcuts. A highly significant (P< 0.01) variation was observed between group 2 and the othertwo groups with respect to Pre- slaughter weight (64.99 ± 0.30 Kg), Carcass length (26.42 ±0.27 inches), Average Back Fat Thickness (1.52 ± 0.03 inches), Hot carcass weight (48.86 ±0.38 Kg), Dressing percentage (75.2 ± 0.39%), Meat - Bone ratio (4.16 ± 0.00), Ham (27.63± 0.22 %) and Belly (8.69 ± 0.15 %). Where as Group 3 was higher in Boston butt and Loinand a highly significant variation (P